Familial correlates of US preschooler physical activity. Issue 2 (3rd April 2019) - Wenhold, Halie; Harrison, Kristen
ABSTRACT: The preschool years set a precedent for lifelong habits integral to health. This research brief investigated how familial correlates within a household context, such as television use, BMI, and feeding practices, are related to child physical activity (CPA). Parents of preschoolers ( N = 278, average age 40–76 months) completed survey measures of CPA, child and parent television use, BMI (height and weight), child control of feeding practices, and parental modeling of child feeding practices. From this sample, parents also had their preschoolers' BMI percentiles calculated by a team of researchers, resulting in 247 complete parent-child pairs. Separate regression analyses revealed that child weekly television use and parent weekly television use predicted less CPA; however, when simultaneously controlling for child and parental correlates, only parent weekly television use predicted less CPA. Post-hoc analyses revealed an interaction between parent and child television use, such that parent-child pairs who reported higher weekly TV use reported less frequent CPA than parent-child pairs who reported lower weekly TV use. Across all regression models, child gender (i.e., female) also predicted less CPA. The discussion explores potential consequences of media familial correlates predicting CPA and parental strategies to encourage CPA.